Convincing methods in designing infographic content analytical study - Al-Rubaye, Bairq Hussein Jumaah (ALBAHITH ALALAMI, 2020)
The research aims to reveal the recent trends used in providing information and to know the persuasive methods used in designing the content of the infographic as well as the nature of persuasive design methods and the topics presented by the infographic in the research sample. The researcher used the survey method, specifically the survey, by using the content analysis method to analyze the infographic material from the sample selected from the press and news sites that are the subject of the research, based on the method of what was said? How was it said? The researcher relied on the intentional sample, and this sample depends on the researcher selecting the vocabulary of the sample based on experiences and evaluating the characteristics that are available in the research sample (Alsumaria News and Mawazine News Agency website), relying on drawing the sample on the method of comprehensive inventory of the sample for a month, which is the period The time set by the researcher to conduct the research and the sample total was 25 infographics. Among the most prominent findings of the research is information richness in the infographic, the research sample in addition to interest in news information and confidence indicators, which is an important element in the quality of infographic information with attention to the quality of design based on statistical, descriptive, composite, interrogative and comparative infographic, and this is an important indicator of the interest of the research sample in the way information is presented , With a preference for the use of video infographic because of its attractive style of presentation as well as the use of fixed infrared is indispensable